AREAS OF BUSINESS ACTIVITY IN THE DEVELOPMENT OF ENVIRONMENTALLY VALUABLE ECO-PRODUCTS - AS EXEMPLIFIED BY THE LUBLIN VOIVODESHIP - Zwolińska-Ligaj, Magdalena (Acta Scientiarum Polonorum. Oeconomia, 2015)
The purpose of this study is to classify the activity of entrepreneurs in the field of the integration of environmental concerns into the various phases of the life cycle of a product/ service and the evaluation of the potential of the selected elements of the organizations important from the perspective of expanding this activity. This paper includes an assessment of the significance of some selected factors in the implementation of business support solutions in the adoption of pro-environmental ideas, and outlines the importance of the location as regards a natural, valuable area for the formation of eco-products. The study revealed no formal basis for the implementation of an eco-product policy and the pro-ecology motivation of half of the entities, resulting mainly from the need for compliance with environmental regulations. Activity in the shaping of eco-products requires a strengthening of the case study group and a more comprehensive approach. Its limitations are financial and information barriers. Most respondents see opportunities for creating organic products as a result of their location.